The Role of Participatory Budgeting in Enhancing Citizen Engagement - Abbasov , Ramil (American Journal of Economics and Business Management, 2025)
Participatory budgeting (PB) has emerged as a transformative approach to local governance, designed to empower citizens by directly involving them in decision-making processes concerning public expenditures. This scientific article examines the role of participatory budgeting in enhancing citizen engagement, drawing upon theoretical perspectives, empirical data, and case studies from diverse municipal contexts. Through a comprehensive literature review, the article delineates the evolution of participatory budgeting—from its pioneering roots in Porto Alegre, Brazil, to its adaptation in various democratic societies worldwide—and underscores its potential to improve transparency, accountability, and democratic legitimacy. Methodologically, the study employs a mixed-methods design, combining quantitative survey data from municipalities with and without participatory budgeting initiatives and qualitative interviews with local government officials and community members. The analysis reveals statistically significant increases in civic participation, trust in local government, and social capital in regions where participatory budgeting is implemented. The discussion section critically evaluates the strengths and limitations of PB practices, addressing issues of scalability, representativeness, and the challenges posed by political and administrative constraints. Concluding with policy recommendations and avenues for future research, this article contributes to the academic discourse by providing an in-depth exploration of how participatory budgeting can serve as a catalyst for broader citizen engagement in the public sphere. The findings suggest that while participatory budgeting is not a panacea for all democratic deficits, it represents a meaningful step towards a more inclusive and responsive form of governance.